An Evaluation to Predict the Probability of Success of Student-Centered Learning in Business School - Taridi Kasbi Ridho; Fitri Yani Jalil (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2022)
AbstractThe purpose of this study was to describe the implementation of student-centered learning, to evaluate its effectiveness and to predict the possibility of success of it in a business school of the Faculty of Economics and Business of Universitas Islam Negeri (State Islamic University) Syarif Hidayatullah Jakarta. A number of questioners were distributed to lecturers and students who experienced in using this method, followed by focused group discussions and in-depth interviews. Results showed that piloting three student-centered learning methods, i.e. learning by case method, project market research, and gamification at the faculty was welcomed by both students and lecturers as they have taken many advantages from it. They gained deeper and wider knowledge. They could improve their critical and creativity thinking, be more independent, responsible, confidence, courage and had better engagement and dedication to learning process, a set of skills required to be successful after graduation. However, challenges to make this new pedagogy method to be fun, easy to understand and deliver optimum result still remained. This paper contributed to improvement of human resources in the private sector especially in emerging countries by showing that applying right pedagogical method together with multi aspects improvement from lecturers, students, and physical infrastructures will enable business school graduates to fulfill the needs and challenges of current and future business world.AbstrakTujuan dari penelitian ini adalah untuk mendeskripsikan implementasi pembelajaran yang berpusat pada siswa, mengevaluasi keefektifannya dan memprediksi kemungkinan keberhasilannya di sekolah bisnis Fakultas Ekonomi dan Bisnis Universitas Islam Negeri (UIN) Syarif. Hidayatullah Jakarta. Sejumlah kuesioner dibagikan kepada dosen dan mahasiswa yang berpengalaman menggunakan metode ini, dilanjutkan dengan diskusi kelompok terfokus dan wawancara mendalam. Hasil penelitian menunjukkan bahwa percontohan tiga metode pembelajaran yang berpusat pada siswa, yaitu pembelajaran dengan metode kasus, riset pasar proyek, dan gamifikasi di fakultas disambut baik oleh mahasiswa dan dosen karena mereka telah mengambil banyak keuntungan darinya. Mereka mendapatkan pengetahuan yang lebih dalam dan lebih luas. Mereka dapat meningkatkan pemikiran kritis dan kreativitas mereka, menjadi lebih mandiri, bertanggung jawab, percaya diri, berani dan memiliki keterlibatan dan dedikasi yang lebih baik dalam proses pembelajaran, seperangkat keterampilan yang dibutuhkan untuk sukses setelah lulus. Namun, tantangan untuk menjadikan metode pedagogi baru ini menyenangkan, mudah dipahami dan memberikan hasil yang optimal masih ada. Makalah ini berkontribusi pada peningkatan sumber daya manusia di sektor swasta terutama di negara-negara berkembang dengan menunjukkan bahwa menerapkan metode pedagogis yang tepat bersama dengan peningkatan multi aspek dari dosen, mahasiswa, dan infrastruktur fisik akan memungkinkan lulusan sekolah bisnis untuk memenuhi kebutuhan dan tantangan saat ini dan dunia bisnis masa depan How to Cite Ridho, T. K., Jalil, F. Y. (2022). An Evaluation to Predict the Probability of Success of Student-Centered Learning in Business School. TARBIYA: Journal of Education in Muslim Society, 9(2), 93-104. doi:10.15408/tjems.v9i1.23189.